Organic Modification of Natural Clay Minerals and Its Adsorption on Anionic PPCPs - Sun, Ken. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book mainly investigates the adsorption of anionic diclofenac sodium on natural clay minerals, the adsorption of anionic chloramphenicol on natural clay minerals and the behavior of surface and interface modification or adsorption on clay minerals. It has significant guidance for learning the transfer and fate of pharmaceuticals and personal care products (PPCPs) in the soil. It develops an efficient, low-cost adsorbent material and provides theoretical basis and valuable reference for the effective prevention of groundwater contamination of PPCPs in the field of environmental engineering.
Introduction -- Adsorption of anionic antibiotics by CTAB modified natural clay minerals -- Study on the adsorption of anionic antibiotics on natural clay minerals modified by ionic liquids -- Molecular Dynamics Simulation of Adsorption of Anionic Antibiotics on Organic Modified Natural Clay Minerals -- Dynamic adsorption experiment of modified zeolite and montmorillonite -- Conclusion.
Keywords: Refuse and refuse disposal; Environmental chemistry; Pollution; Mineralogy; Environmental engineering; Biotechnology; Bioremediation; Water; Hydrology; Waste Management/Waste Technology; Environmental Chemistry; Pollution; Mineralogy; Environmental Engineering/Biotechnology.; Water